Pengaruh Pola Makan terhadap Status Gizi Narapidana Lapas Kelas II A Baubau - Asmarani Asmarani; I Putu Sudayasa; Ade Ratna Dewi (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2018)
ABSTRACT Background: Fulfillment of food is a human need to maintain its life and carry out daily activities, the law Number 12 of 1995 Article 14 mandates that prisoners are entitled to health services and adequate food. Research Purpose: This study aims to determine the effect of diet on nutritional status of prisoners in prison Class II A Baubau. Research Method: The study was conducted in February of 2018 at the Class II A Baubau Prison Center on 132 prisoners. The research method used was observational analytics with cross sectional approach by measuring body weight and height also interview using questionnaire. The data of the research were analyzed using chi square test. Research Result: The results showed that 23.5% of respondents were nutritional status of thin, 65.9% normal nutritional status and 10.6% of respondents had more nutritional status. Prisoner diet was found that 82.6% of respondents get food according to the prison regulations and 17.4% of respondents get food not in accordance with prisons. Chi square test showed that there is influence of diet to nutritional status of prisoner shown with value P = 0.000. Conclusion: The conclusion of this research, that there was a dietary influence on the nutritional status of prisoners of Class II A Baubau. It was expected that the government and the prisons can pay attention to the intake of nutrients received by prisoners to achieve optimal prison health and coaching processes.Keywords: Prison, Inmates, Dietary Habit, Nutritional Status